African Union : legal and institutional framework, a manual on the Pan-African Organization legal and institutional framework, a manual on the Pan-African Organization - Yusuf, Abdulqawi; Ouguergouz, Fatsah, 1958- (Leiden : Martinus Nijhoff Pub. : Brill, 2012)
This work is an introduction into the origins, law and institutions of the African Union (AU). It examines the evolution, structures, legal standards and operational activities of this Pan-African organization, which replaced the Organization of African Unity (OAU) ten years ago.
C. Protocols on Amendments to the Constitutive Act of the African UnionD. Links to the African Union Organs, Agencies and Instruments.
Keywords: African Union; African Union; Since 1960; African cooperation; Law -- International; African cooperation; Political science; Africa -- Politics and government -- 1960-; Africa